Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Show that each statement is true:
Cos^4X-sin^4X=2cos^2X-1


Sagot :

luana
[tex]cox^4x-sin^4x=2cos^2x-1\\\\ (cosx^2-sin^2x)(cosx^2x+sin^2x)=2cos^2x-1\\\\ cosx^2-sin^2x*1=2cos^2x-1\ \ \ | subtract\ 2cos^2x\\\\ -cosx^2-sin^2x=-1\ \ \ | multiply\ by\ -1\\\\ cosx^2+sin^2x=1\\\\ 1=1[/tex]